A novel theory for designing SI engines based on exergy efficiency, entropy, octane rating, and fuels’ physicochemical properties for Otto cycles - Gómez Montoya, Juan Pablo (2024)
It is presented a novel theory for designing spark ignition (SI) engines based on tests in three SI engines, three scientific methodologies, and thermodynamics laws applied to Otto cycles. Mathematical modeling used the optimal thermal efficiency for the Otto cycle and data on octane rating for liquid fuels and the methodology for methane number for gaseous fuels. Before, two methodologies had been developed for quantitative estimation of energy quality and exergy efficiency for gaseous fuels in SI engines. Equations are proposed to correlate exergy efficiency, entropy, energy recovered, maximum thermal efficiency, and certain fuel physicochemical properties for SI engines. Also, tests and correlations between fuel properties and octane rating are presented to validate the hypothesis. Besides, it presented the performance data of an SI engine converted and optimized for biogas, which was designed and scaled based on this theory. The engine has a high compression ratio with pistons selected for high turbulence, getting greater output power and efficiency with biogas compared with diesel and natural gas. Due to biogas’s physicochemical properties (the highest-octane rating, low energy density, low laminar flame speed, and low adiabatic flame temperature), its combustion resulted at high pressure and high turbulence intensity with better performance than diesel oil. According to exergy efficiency for internal combustion engines is better to use biogas, biomethane, and natural gas instead of fuels like diesel and gasoline.